Analysis of the Sectoral Stock Price Index on the IDX during the Covid-19 - Arman, Agus; Suade, Yuyun Karystin Meilisa (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
In this study, we want to measure the performance of the average monthly return of sectoral stock indexes in Indonesia by using the composite index (JCI) as a comparison. We want to find the winner, loser, and neutral stock indexes. We use monthly data from March 2020 to February 2021, namely the sectors: agriculture, mining, essential industry, various industries, consumption, property, infrastructure, finance, and trade. We use panel data analysis from the event study to achieve the research objectives, a combination of cross-section data and time-series data. The research results showed six sectors of the stock index as winners: agriculture, mining, essential industry, infrastructure, finance, and trade. There are three loser stock index sectors: the miscellaneous sector, consumption, and property.